Demand for Information for Wildland Fire Management - George B. Frisvold; Ning Zhang; Michael A. Crimmins; Daniel Ferguson; Charles Maxwell (Atmosphere)
Significant resources have been devoted to increasing the supply of data and information products for wildland fire management. There has been comparatively less emphasis on understanding the demand for these products. There are large differences in the number of information sources that fire managers use in decision making. We developed a value-of-information model for wildland fire managers to formulate hypotheses about what factors drive these differences. Data from a comprehensive internet survey targeting a well-defined population of the Southwest wildland fire managers are used to test these hypotheses. Results are generally consistent with hypotheses generated from the value-of-information model. Multiple regression results suggest information use increases with the number of decisions that managers make and is greater during fire season than before. Information use is affected by a manager’s level of education, age, experience, job type, the agencies they work for, and the multi-agency dispatch centers where they work. Agency and dispatch center effects explain more of the variation in information use than differences in the respondents’ personal characteristics. To better understand fire manager demand for information, future research could explore in more detail what specific attributes of agencies and dispatch centers affect use of information for wildland fire management.